2023
DOI: 10.3390/medicina59030512
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic Syndrome and Statin Therapy: An Outcome Analysis

Abstract: Background and Objectives: Hypercholesterolemia in patients with nephrotic syndrome (NS) may predispose to cardiovascular events and alter kidney function. We aimed to evaluate statins efficiency in NS patients under immunosuppression using four endpoints: remission rate (RR), end-stage kidney disease (ESKD), major cardiovascular events (MACE), and thrombotic complications (VTE). Materials and Methods: We retrospectively examined the outcome at 24 months after diagnosis of 154 NS patients (age 53 (39–64) years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…Consistent with those results, post hoc lipid analyses using a limited number of available samples from this study also suggested dose‐dependent increases in total cholesterol, LDL‐C, and HDL‐C. These observations are likely related to reductions in serum albumin, 13,14 and were reversible upon discontinuation of the drug. Moreover, preliminary results from a study in healthy volunteers have shown that lipid increases with batoclimab treatment may be prevented by co‐administration of atorvastatin 15…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with those results, post hoc lipid analyses using a limited number of available samples from this study also suggested dose‐dependent increases in total cholesterol, LDL‐C, and HDL‐C. These observations are likely related to reductions in serum albumin, 13,14 and were reversible upon discontinuation of the drug. Moreover, preliminary results from a study in healthy volunteers have shown that lipid increases with batoclimab treatment may be prevented by co‐administration of atorvastatin 15…”
Section: Discussionsupporting
confidence: 87%
“…It primarily affects the pediatric population with a reported incidence of 2-7 cases per 100,000 children (1). While the cause of NS in pediatric patients is often idiopathic, inflammation and oxidative stress have been implicated in its pathogenesis and complications (1,2). Glucocorticoids are the primary treatment for idiopathic NS, leading to clinical remission in the majority of patients within 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress denotes the state of imbalance between reactive oxygen species (ROS) and the antioxidant system that eliminates them, resulting in compromised cellular signaling and cell damage (7). Oxidative stress can contribute to the development and progression of NS by damaging the glomerular filtration barrier, promoting inflammation, altering lipid metabolism, impairing endothelial function and causing cellular damage (2,8). Several studies have shown that NS patients experience high levels of oxidative stress during the acute phase of the condition, and some studies have reported that oxidative stress markers remain elevated even after steroidinduced remission of the disease (7,9,10).…”
Section: Introductionmentioning
confidence: 99%